Challenge of Firearms Control in a Free Society. Issue 2 (19th April 2018) - Cook, Philip J.
Abstract: Chapter 10 of The Challenge of Crime in a Free Society, titled "Control of Firearms, " is a brief but strong statement in support of regulating gun transactions, possession, and carrying, with several specific recommendations, including the adoption of universal gun registration and permit‐to‐purchase requirements. The U.S. President's Commission on Law Enforcement and Administration of Justice, when writing the chapter, had no systematic research to draw on. Since its publication in 1967, the field of gun violence has become an active area of research, and much has been learned. But the nation has become far more polarized politically during the last 50 years, and gun policy has become a rigidly partisan issue. A new commission would have great difficulty reaching consensus, although there may be common ground on regulating guns vis‐à‐vis mental illness and domestic violence.